(untitled) (Journal of Scientific Research, 2012)
Dehulled cotyledons of Jack beans (Canavalia ensiformis, L) were thermally treated by roasting and pressure cooking, allowed to deteriorate for seven days and the microorganisms involved isolated and identified.. This was after five days of natural solid state fermentation, using the natural micro flora of the air and banana leave used in wrapping. The physiochemical compositions of the deteriorated cotyledons were monitored. There was a significant increase in the microbial count for the first three days of deterioration followed by gradual decrease. A total of eighteen bacteria were isolated however Bacillus subtilis, Leuconostoc lactic, Leuconostoc meseneroides, Listeria denitrificans, Listeria murrayii and Xanthomorias fragariae were dominant in all the samples. A total of eight fungal isolates were involved which were all dominant except Geniculosporium serpens found in pressure cooked ground sample. All treated samples had higher protein content than the control but the carbohydrate content was significantly low when compared with the control; however there was a significant decrease in the antinutrient content of the treated samples when compared to the control. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.8684 J. Sci. Res. 4 (3), 689-700 (2012)